2002
DOI: 10.1007/s11746-002-0614-3
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and properties of lipase from germinating seeds of Jatropha curcas L.

Abstract: Lipase present in the seeds of Jatropha curcas L. was isolated and some of its properties studied. Lipase activity was detected in both dormant and germinating seeds. The lipase was partially purified using a combination of ammonium sulfate precipitation and ultrafiltration, which increased the relative activity of the lipase by 28-and 80-fold, respectively. The lipase hydrolyzed palm kernel, coconut, and olive oils at comparable rates (approximately 5 µg FFA/µg protein/min); palm-Raphia hookeri and Jatropha c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
9
31
2
2
Order By: Relevance
“…Seed lipases from Jatropha curcas L., also known as Barbados nut, were studied by Abigor et al (2002). The lipase was partially purified using a combination of ammonia sulphate precipitation and ultrafiltration.…”
Section: Barbados Nut Lipases (Jatropha Curcas L)mentioning
confidence: 99%
“…Seed lipases from Jatropha curcas L., also known as Barbados nut, were studied by Abigor et al (2002). The lipase was partially purified using a combination of ammonia sulphate precipitation and ultrafiltration.…”
Section: Barbados Nut Lipases (Jatropha Curcas L)mentioning
confidence: 99%
“…In others works from the literature, Enujiugha et al (2004) found that Calcium ion in the reaction mixture brought about 64% increase in activity of lipase activity in dormant seeds. Abigor et al (2002) and Haas et al (1992) also observed an enhancement of lipase activity by calcium ion inclusion. From the work of Mukundan et al (1985), the chloride ion did not cause any inhibitory effect but the metal ions (Na + , Hg 2+ ) enhanced lipase decrease.…”
Section: Na = Not Availablementioning
confidence: 87%
“…The purification process resulted in 2.8-fold purification and a final yield of 80% of the enzyme with a specific activity of 940 U/mg. Abigor et al, (2002) [19] also reported that the lipase enzyme produced from Jatropha curcas purified with 80% ammonium sulfate precipitation achieved a 2.8-fold increase in the relative activity of the lipase in the supernatant.…”
Section: Ammonium Sulfate Purification Of Lipase Enzymementioning
confidence: 93%